Stages of change for fruit and vegetable intake among New Zealand men: Readiness to eat five servings a day and impact of contextual factors - Jury A; Flett R (Men's Studies Press, LLC, 2010)
Successful behavior change according to the transtheoretical model involves progressing through a series of stages of change. This paper examines the proportion of men in each stage of change for fruit and vegetable intake, compares stage classification with intentions and behavior, and the impact of contextual factors on stage membership. Men randomly selected from the New Zealand electoral roll completed a postal questionnaire (n = 518; 45% response rate). One-third (32%) of respondents were not intending to eat five or more servings of fruit and vegetables a day (precontemplation stage), 10% were contemplating change (contemplation stage), 7% preparing to change (preparation stage), and 51% were already doing so in the combined action/maintenance stage. Intentions increased on average across stages, and fruit and vegetable intake was at least two servings higher in action/maintenance. Dietary guideline knowledge, older age, higher income, education and food security increased the likelihood of being in action/maintenance. Simple health promotion messages should be directed toward men, promoting conventional and affordable produce, and dietary guidelines. Community and policy approaches that increase food skills and knowledge, fruit and vegetable access and affordability would support behavior change.
Keywords: fruit and vegetable; stages of change; transtheoretical model; 1117 Public Health and Health Services; 1701 Psychology